The Impact of Social Media Influencers Towards Consumers’ Attitude - Tan, Kristine, Kai Qing; Soon, Eu Hui; Sriganesh, Varun (INTI International University, 2024)
The rapid evolution of marketing trends is closely tied to the increasing use of social media, driven by advancements in technology and the preferences of the younger generation. Brands are increasingly leveraging the influence of social media personalities as endorsers, making social media influencer marketing one of the most prevalent and effective strategies for promoting products and services. Compared to traditional marketing methods, influencer marketing has demonstrated greater effectiveness in shaping consumer attitudes and behaviors. This study examines the impact of social media influencers on consumers’ attitudes, focusing on the Malaysian context. Data were collected through an online survey to explore how influencer marketing influences purchasing decisions. The findings reveal that consumers are more inclined to trust and purchase products endorsed by influencers than those promoted through official advertising. By analyzing the role of influencers in shaping consumer attitudes, this research underscores the importance of promoting responsible consumption patterns, aligning with Sustainable Development Goal 12 (SDG 12). The study advocates for brands and influencers to encourage ethical consumption and sustainable practices, ensuring that marketing efforts contribute to the broader goal of achieving sustainable production and responsible consumer behavior.